The shifting care and outcomes for patients with endangered limbs – Critical limb ischemia (SCOPE-CLI) registry overview of study design and rationale. (April 2022) - Scierka, Lindsey E.; Mena-Hurtado, Carlos; Shishehbor, Mehdi H.; Spertus, John A.; Nagpal, Sameer; Babrowski, Trissa; Bunte, Matthew C.; Politano, Amani; Humphries, Misty; Chung, Jayer; Kirksey, Lee; Alabi, Olamide; et al.
Abstract: Background: Critical limb ischemia (CLI), the most severe form of peripheral artery disease, is associated with pain, poor wound healing, high rates of amputation, and mortality (>20% at 1 year). Little is known about the processes of care, patients' preferences, or outcomes, as seen from patients' perspectives. The SCOPE-CLI study was co-designed with patients to holistically document patient characteristics, treatment preferences, patterns of care, and patient-centered outcomes for CLI. Methods: This 11-center prospective observational registry will enroll and interview 816 patients from multispecialty, interdisciplinary vascular centers in the United States and Australia. Patients will be followed up at 1, 2, 6, and 12 months regarding their psychosocial factors and health status. Hospitalizations, interventions, and outcomes will be captured for 12 months with vital status extending to 5 years. Pilot data were collected between January and July of 2021 from 3 centers. Results: A total of 70 patients have been enrolled. The mean age was 68.4 ± 11.3 years, 31.4% were female, and 20.0% were African American. Conclusions: SCOPE-CLI is uniquely co-designed with patients who have CLI to capture the care experiences, treatment preferences, and health status outcomes of this vulnerable population and will provide much needed information to understand and address gaps in the quality of CLI care and outcomes. ClinicalTrials.gov identifier (NCT Number): NCT04710563 https://clinicaltrials.gov/ct2/show/NCT04710563.